Specific surface area of polydispersions as a function of size distribution sharpness - PAULO FILIPE T. LOPES; JOSÉ AURÉLIO M. DA LUZ; FELIPE O. MILHOMEM (Anais da Academia Brasileira de Ciências, 2020)
Abstract Knowledge of particulate system properties is very important in various industrial instances and the possibility of fast predicting the behavior of such systems is an important control tool. The specific surface area of simulated particulate systems was studied as a function of the sharpness parameter of the size distribution of the Gates–Gaudin-Schumann, Gaudin–Meloy and Rosin–Rammler equations. The results showed good statistical adherence, especially the Rosin–Rammler equation, in situations where it is the best descriptor of particle size distribution.